Tingkat Pengetahuan Masyarakat tentang Obat Tradisional setelah Pemberian E-Booklet di Kabupaten Karimun - Dewi, Ratna Sari; Pratiwi, Putri Qurnia; Febrina, Mira; Agistia, Nesa (Jurnal Kefarmasian Indonesia, 2022)
Knowledge of traditional medicine is important for the formation of a person's activity in using traditional medicine. Preliminary studies conducted show the level of public knowledge about traditional medicine in the less category. This can be caused by a lack of desire to seek information and lack of education from health workers. For this reason, educational media such as e-booklets are needed. This study aims to see the level of public knowledge about traditional medicine after being given an e-booklet. This study uses a preexperimental method with a one group pretest-posttest design. The population of this research is the residents of Karimun Regency who have used traditional medicine. The sample of this study was 150 respondents who were determined using purposive sampling method. The inclusion criteria for the study were that the respondent was at least 18 years old, had used traditional medicine with the logo and was registered with BPOM for at least the last 3 months, could use a smartphone and was willing to be a respondent. The research instrument is e-booklet media and knowledge questionnaire. The knowledge questionnaire used has been tested for validity and reliability (obtained 20 valid questions with an r value of 0.881). Uni-variate data analysis to describe the level of knowledge and bi-variate analysis was carried out for the analysis of changes in pretest and post-test knowledge scores using the Wilcoxon test. The results obtained before giving the e-booklet are good knowledge as much as 6.6%, sufficient as much as 55.4% and less as much as 38% while after being given the e-booklet the knowledge of respondents with good category is 55.4%, enough is 38% and less as much as 6.6%. Bi-variate analysis obtained p value 0.000. It can be concluded that the given media has a significant effect on respondents knowledge.